Utilization Conventional Market Waste on Catfish Food Production - Zuhra, Cut Fatimah; Lenny, Sovia; Zaidar, Emma; Taufik, Muhammad (Talenta Publisher, 2020)
Tamora Catfish Company as a Micro, Small and Medium Enterprise (UMKM) which one of the Universitas Sumatera Utara community service partners, used a simple microbubble technology system to increase the dissolved oxygen content in pond water in order to anticipate of the large number of die fish because of the polluted pond water, which impacted in reducing the amount of oxygen. Biofloc application was observed decreasing the ammonia content and generating natural feed. This was analyze by the team that already implemented this simple technology in the first year observation which found its successfully reduce fish mortality and increase the number of catfish. However, the catfish food is expensive because it is depend on pellet feed, so the production process costs are very high. Via a multi-year system, community service team utilizes conventional market waste as a feed in order to replace the use of costly pellet feed. The solution was starting from processing conventional market waste such as vegetables waste. It was considered because it is cheap and it needs simple machine technology to produce the feed. The machine will construct by copper and mixer in order to produce feed that suitable for catfish food. Furthermore, it also impacted to make conventional market cleaner from waste since partners collect and process the waste directly.